A home-based lower limb-specific resistance training programme for patients with COPD: an explorative feasibility study. Issue 2 (10th June 2019) - Cook, Hannah; Reilly, Charles C.; Rafferty, Gerrard F.
Peripheral muscle weakness leading to poor exercise tolerance is a significant problem in patients with chronic obstructive pulmonary disease (COPD). Increased lower limb strength following pulmonary rehabilitation (PR) has been shown to be associated with positive outcomes [1]. Despite this, access to and completion of PR remains problematic and alternative exercise interventions are sought. Elastic band resistance training has recently been shown to be as effective as conventional outpatient free-weight exercise training [2–4]. Elastic band resistance training may, therefore, provide an alternative home-based exercise intervention for patients with COPD who are unable or unwilling to participate in PR due to significant symptom burden or anxiety in attending group classes It is feasible and acceptable to deliver a home-based lower limb-specific resistance training (LLSRT) programme to patients with COPD. Individual patient improvements in walking distance and breathlessness severity were observed post-LLSRT intervention. http://bit.ly/30xYpWI